Antiquorum-Sensing and Antibacterial Activity of Green Synthesized Silver Nanoparticles against Methicillin-Resistant Staphylococcus aureus (MRSA) - Arunkumar, M.; Farjeen, M. Safana; Divya, S. K.; Jeyadoss, T. (Challenges and Advances in Pharmaceutical Research Vol. 1, 2022)
The development of efficient methods for the green synthesis of silver nanoparticles using plant extracts has emerged as a major area of focus in nanotechnology. Bactericidal nanomaterials are becoming increasingly important as bacteria develop resistance to even the most potent antibiotics. The discovery of a bacterial communication system (Quorum-sensing system), which orchestrates important temporal events during the infection process, has provided a novel opportunity to treat bacterial infection by means other than growth inhibition. This has promoted research in the well-known bactericidal activity of Ag+ ions and Ag-based compounds, including silver nanoparticles (AgNPs). In the present study, the extracellular biosynthesis of silver nanoparticles was carried out using aqueous extracts of nine different herbal plant leaves for the reduction of aqueous silver ions. Among the nine selected medicinal plants, the leaf extracts of Aerva lanata showed rapid reduction (2 min) of silver ions in the solution. Transmission electron microscopy, UV-visible spectroscopy, and X-ray diffraction were used to examine the nanoparticles' morphology and structures. SEM and X-ray diffraction (XRD) analysis revealed the nanocrystalline phase of silver with average particle sizes ranging from 37 to 47 nm and found to be spherical. Moreover, the synthesized AgNPs demonstrated potent antibacterial activity against Methicillin Resistant Staphylococcus aureus (MRSA). Furthermore, the stable silver nanoparticles inhibited violacein production, which is a quorum-sensing regulated behaviour in Chromobacterium violaceum CV026.